2016
DOI: 10.1530/erc-16-0049
|View full text |Cite
|
Sign up to set email alerts
|

Clonal origin and spread of metastatic prostate cancer

Abstract: Metastatic disease is responsible for the majority of prostate cancer deaths. The standard treatment for metastatic disease is surgical or chemical castration in the form of androgen deprivation therapy. Despite initial success and disease regression, resistance to therapy ultimately develops and the disease transitions to castration resistant prostate cancer, which is uniformly fatal. Thus, developing an understanding of genetic evolution in metastasis and in response to therapy has been a focus of recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…However, although the hypothesis that each metastasis originates from a single tumor cell is generally supported, several studies have supported the existence of polyclonal seeding from an interclonal cooperation between multiple subclones. These latter findings bring insights to find the “true” index lesion by looking on genetic, epigenetic and proteomic alterations ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 90%
“…However, although the hypothesis that each metastasis originates from a single tumor cell is generally supported, several studies have supported the existence of polyclonal seeding from an interclonal cooperation between multiple subclones. These latter findings bring insights to find the “true” index lesion by looking on genetic, epigenetic and proteomic alterations ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have shown that DNA is shed into the blood stream of advanced metastatic castration resistant prostate cancer (CRPC) and this circulating DNA can be used as a marker (Wyatt et al, 2017) (Ritch andWyatt, 2018) (Annala et al, 2018). CRPC is u)niformly fatal disease (Van Etten and Dehm, 2016). These studies did not identify (or categorize metastatic cell.…”
Section: Discussionmentioning
confidence: 95%
“…Mutation enables cancer cells to sustain chronic proliferation in invasive and metastatic cells whereas benign prostate and benign prostatic hyperplasia (BPH) do not have that advantage (Hanahan and Weinberg, 2011) (Bryden et al, 2001) (Scholzen and Gerdes, 2000) (Lindboe and Torp, 2002). Metastatic disease is responsible for majority of PC deaths (Van Etten and Dehm, 2016). Metastasis usually occurs in about 10% PC patients indicating metastatic inefficiency (Weiss, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it has approved that multiform clonal origins exist in malignant tumor. Identifying the clonal origin is of great significance for exploring tumor occurrence and evaluating tumor evolution [18][19][20][21][22] . For solidary tumor, there are two types of clonal origin, monoclonal origin and polyclonal origin [23] .…”
Section: The Clonal Origin Of Hccmentioning
confidence: 99%